2021
DOI: 10.3390/nu13020323
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Serum Vitamin D Levels in the Assessment of IBD Activity and Response to Biologics

Abstract: The main role of vitamin D is calcium homeostasis and bone metabolism, although its activity as an immuno-modulator and its anti-inflammatory effect is well-known. Low blood vitamin D levels are common among patients with inflammatory bowel disease (IBD). Whether low vitamin D levels could affect the disease activity or it is an effect of a worse condition of the disease is still unclear. This study aimed to investigate the role of blood vitamin D levels to identify the clinical, endoscopic, and histological a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…Mucosal healing is perceived an important treatment goal in CD [27]. Another IBD study demonstrated that vitamin D deficiency was associated with disease activity and loss of clinical response to biological treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Mucosal healing is perceived an important treatment goal in CD [27]. Another IBD study demonstrated that vitamin D deficiency was associated with disease activity and loss of clinical response to biological treatment [28].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced risk of postoperative endoscopic recurrence in patients with CD who underwent surgery has been reported in an observational study in patients with vitamin D > 30 ng/mL (OR 0.22, 95% CI 0.07-0.66, p = 0.006) [99]. Thus, vitamin D has been proposed as a potential biomarker of disease activity [98,100]. This is, at best, debatable, as vitamin D concentration reflects changes occurring over relatively long periods.…”
Section: Vitamin D Supplementation and Disease Coursementioning
confidence: 89%
“…A correlation between vitamin D levels and disease activity is also present [30]. Levels of 25(OH)D ≤ 25 ng/mL in a retrospective study had an AUC of 0.79-0.81 for the identification of endoscopic and histologic activity [98]. Reduced risk of postoperative endoscopic recurrence in patients with CD who underwent surgery has been reported in an observational study in patients with vitamin D > 30 ng/mL (OR 0.22, 95% CI 0.07-0.66, p = 0.006) [99].…”
Section: Vitamin D Supplementation and Disease Coursementioning
confidence: 95%
See 1 more Smart Citation
“…However, the ultimate goal to achieve a stable clinical remission is far from being reached. In this scenario, a growing number of adjunctive therapies, such as vitamin D and probiotics, has been proposed over the years, integrating the current standard of care in the hope of achieving clinical benefits [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%